Data Management Plans as a Research Tool. Issue 5 (3rd August 2015) - Rolando, Lizzy; Carlson, Jake; Hswe, Patricia; Parham, Susan Wells; Westra, Brian; Whitmire, Amanda L.
Abstract : EDITOR'S SUMMARY The growing recognition of and demand for formal data management plans (DMPs) is spurring academic and research libraries to consider how they can serve researchers to meet this need. Research data management services may include training in data management, consultation for plan writing and support with metadata elements and data repository choice. Libraries must develop expertise in research data management in the absence of clear or consistent guidance or practice, but useful direction is available through researchers' DMPs. The authors, representing several universities, collaborated on the development of a rubric to analyze and evaluate DMPs required by the National Science Foundation. Analysis of these DMPs, drawn from varied institutions, illustrates existing practices and has led to an assessment tool that can help libraries determine the services they should be able to offer researchers.